Layanan Informasi Dalam Pencegahan Stunting Di Desa Manyabar Jae - Asmaryadi Asmaryadi (Marpokat: Jurnal Pengabdian Kepada Masyarakat, 2023)
AbstractInformation services function to equip individuals with various knowledge and understanding of various things that are useful for individual self-actualization. Stunting is a problem of chronic malnutrition caused by a lack of nutritional intake for a long time, resulting in impaired growth in children, namely lower child height. or short (dwarf) for the standard age. The condition of a short child's body is often said to be a hereditary (genetic) factor from both parents, so that many people just accept it without doing anything to prevent it. In fact, as we know, genetics is a determinant factor for health that has the least influence when compared to behavioral, environmental (social, economic, cultural, political) factors, and health services. The purpose of implementing this community service through this information service is stunting prevention. The results and conclusions can be understood that healthy behavior is not only influenced by knowledge but is influenced by attitudes towards understanding problems, access to health services and environmental conditions. healthy lifestyle is very important and useful.   Keywords: information services; stunting prevention; health; cleanliness.   Abstrak Layanan informasi berfungsi untuk membekali individu dengan berbagai pengetahuan dan pemahaman tentang berbagai hal yang berguna untuk aktualisasi diri individu  Stunting adalah masalah kurang gizi kronis yang disebabkan oleh kurangnya asupan gizi dalam waktu yang cukup lama, sehingga mengakibatkan gangguan pertumbuhan pada anak yakni tinggi badan anak lebih rendah atau pendek (kerdil) dari standar usianya. Kondisi tubuh anak yang pendek seringkali dikatakan sebagai faktor keturunan (genetik) dari kedua orang tuanya, sehingga masyarakat banyak yang hanya menerima tanpa berbuat apa-apa untuk mencegahnya. Padahal seperti kita ketahui, genetika merupakan faktor determinan kesehatan yang paling kecil pengaruhnya bila dibandingkan dengan faktor perilaku, lingkungan (sosial, ekonomi, budaya, politik), dan pelayanan kesehatan. Tujuan pelaksanaan pengangabdian kepada masyarakat ini melalui layanan informasi ini dapat pencegahan stunting.Hasil dan kesimpulan dapat dipahami bahwa perilaku sehat tidak hanya dipengaruhi oleh pengetahuan tetapi dipengaruhi oleh sikap terhadap memahami masalah, akses pelayanan kesehatan dan kondisi lingkungan. perilaku hidup sehat itu sangat penting dan berguna.Kata Kunci: layanan informasi; pencegahan stunting; kesehatan; kebersihan.